Design and Optimization of a Planar Biped Leg Based on Direct Drive Linear Actuators. (28th June 2022) - Langard, M.; Lucidarme, Ph.; Delanoue, N.; Guyonneau, R.; Mercier, F.; Chevallereau, C.; Wenger, Ph.; Aoustin, Y.
Abstract : The choice of actuation when designing a bipedal robot is an important matter, as it impacts its capacities and its control. In these aspects, electric direct-drive (DD) linear motors are interesting candidates. Indeed, they can reproduce the human muscle system by using monoarticular and bi-articular motors and offer a natural backdrivability for impact mitigation. However, motor efficiency depends on their elongation and their attachment points. The ROBIBIO (RObot humanoïde BI-articulaire BIO-inspiré) project aims to design and build a planar bipedal robot using electric direct-drive linear motors for the actuation. To do so, a simulator was developed to evaluate multiple human-like bipedal robot architectures over a set of motion-captured movements. Furthermore, a numerical optimization was done to find the best motor placement for each architecture.